Using Exploratory Focus Groups to Inform the Development of Targeted COPD Self-Management Education DVDs for Rural Patients - Michael Stellefson; Beth H. Chaney; J. Don Chaney (International Journal of Telemedicine and Applications)
This exploratory study assessed the self-management learning needs, experiences, and perspectives of COPD patients treated at a Certified Federal Rural Health Clinic to inform the development of a COPD self-management DVD. A purposive, homogeneous sample of COPD patients participated in focus group interviews. Data from these interviews were referenced to edit a library of Rvision COPD self-management DVDs into a single condensed DVD containing only the most pertinent self-management topics. Patients reported a lack of knowledge and skill development related to purse lipped breathing, controlled coughing, and stress management; while medication management skills were found to be quite adequate. Engaging rural communities in formal qualitative inquiries to describe COPD specific needs for self-management may lead to future use of educational technologies aimed at improving quality of life for these rural, hard to reach populations.